Milk Bar: kids only - Tosi, Christina; Hargreaves, Henry (New York : Clarkson Potter/Publishers, 2020)
"Dedicated to the next generation of young bakers, Milk Bar: Kids Only presents more than eighty-five fun and empowering recipes to inspire imagination in the kitchen, from Apple Pie Waffles to PB&J Cereal Treats to Strawberries and Cream Cupcakes to marshmallowy Choco Crunch Cookies. This is a cookbook that teaches kitchen skills and also shows bakers the brilliance of what a little personality can bring to the mix. Whether they're transforming a donut into a milkshake or creating their own flavored butters for smearing onto biscuits, readers will have plenty of opportunities for mixing and matching within recipes to help their creativity run wild"--
Recipes by type -- Introduction -- Rules of the kitchen -- Pantry 411 -- Tools of the trade -- Measuring 101: wets, dries, and doneness -- Help hotline! -- The recipes.
Includes index.
Ages 6-16
108481
Keywords: Momofuku Milk Bar; Baking. -- Juvenile literature; Desserts; Cookbooks